Pemanfaatan Pupuk Organik Plus Batubara (Baraplus) pada Beberapa Varietas Jagung Manis di Lahan Ultisol - Marlina, Neni; Midranisiah, M; Syafrullah, S; Hafid, Harapin (Journal Galung Tropika, 2022)
Ultisol as agricultural land has low fertility which is characterized by pH, cation exchange capacity, nutrient availability, and very low organic matter content, thus inhibiting plant growth and production. To overcome the low productivity of these ultisols, it is necessary to improve soil fertility, which includes improving the physical, chemical, and biological properties of the soil. Soil fertility can be improved by using organic fertility plus coal (baraplus) which contains nutrients N, P, K, and micronutrients as well as using high-yielding varieties. This research was conducted in Sukarame sub-district, Palembang city starting from October to December 2018. Research method using field experiment method. Lay out the chart in the field using a spit plot with 9 treatment combinations repeated 3 times. The main plot, namely the types of varieties: bonanza, sweet boy, master sweet. As sub-plot, namely the dose of organic fertilizer plus: 500kg/ha, 1000 kg/ha, 1500 kg/ha. The results showed that the treatment with a dose of organic fertilizer plus 1500 kg/ha with the master sweet variety resulted in the highest production of 8.42 kg/plot or the equivalent of 22.45 tons/ha.